Interventions to Dispel Neuromyths in Educational Settings—A Review - Rousseau, Luc (Frontiers in Psychology, 2021)
Neuromyths are misconceptions about the brain and learning (e.g., Students are either “left-brained” or “right-brained”; Tailoring instruction to students’ preferred “learning styles” promotes learning). Recent reviews indicate that the prevalence of beliefs in neuromyths among educators did not decline over the past decade. Potential adverse effects of neuromyth beliefs on teaching practices prompted researchers to develop interventions to dispel these misconceptions in educational settings. This paper provides a critical review of current intervention approaches developed to dispel neuromyths in samples of in-service and pre-service teachers. The following questions are examined. Does neuroscience training provide student teachers with a “protection shield” against neuromyths? Are refutation-based interventions effective, and observed effects enduring in time? Are reduced beliefs in neuromyths translate in the adoption of more evidence-based teaching practices? Are teachers’ professional development training workshops and seminars on the neuroscience of learning effective at instilling more neuroscience in the classroom? Challenges, issues, controversies, and gaps in current research are highlighted, notably the so-called “backfire effect,” the social desirability bias, and the need for behavioral evidence. Future directions are outlined.